Robust Stabilization of a Non-Linear Chaotic Financial System with Uncertain Parameters - Kumar Choudhary, Santosh; ., . (International Journal of Engineering and Technology, 2018)
The paper investigates an analytical approach for robust stabilization of nonlinear chaotic financial system in the presence of uncertain parameters. The primary focus of this paper is to find a robust solution for quickly adjusting and controlling the interest rate, investment demand and price exponent when the chaotic phenomenon occurs in the financial system or economic crisis happens. The paper first demonstrates the non-linear dynamical model of the chaotic financial system and then it adopts Lyapunov stability theory based adaptive control scheme for robust stabilization of nonlinear chaotic financial system in the presence of uncertain parameters. Numerical simulations are demonstrated to verify the effectiveness of the proposed control scheme. The simulation results of this paper show that control scheme successfully eliminates the chaos of the nonlinear financial systemsÂ Â